2008
DOI: 10.1007/s00299-008-0569-y
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of transgenic Cryptomeria japonica D. Don after Agrobacterium tumefaciens-mediated transformation of embryogenic tissue

Abstract: A genetic transformation procedure for Cryptomeria japonica was developed after co-cultivation of embryogenic tissues with the disarmed Agrobacterium tumefaciens strain C58/pMP90, which harbours the visual reporter gene sgfp and two selectable marker genes, hpt and nptII. We were able to generate eight and three independent transgenic lines per gram of embryogenic tissue after selection on hygromycin and kanamycin medium, respectively. Transgenic plants were regenerated through somatic embryogenesis in 4 lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…Genetic modification might be a powerful tool to shorten the time needed to breed trees compared with traditional breeding methods because it is able to induce the favorable traits by introduction of specific genes in trees without unnecessary genetic transitions. A method for Agrobacterium tumefaciens-mediated transformation of embryogenic tissue was recently developed for C. japonica (Taniguchi et al 2008). Introduction of a male sterile trait by genetic modification of C. japonica is a viable approach to address the medical and public health problems of C. japonica polleninduced pollinosis.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic modification might be a powerful tool to shorten the time needed to breed trees compared with traditional breeding methods because it is able to induce the favorable traits by introduction of specific genes in trees without unnecessary genetic transitions. A method for Agrobacterium tumefaciens-mediated transformation of embryogenic tissue was recently developed for C. japonica (Taniguchi et al 2008). Introduction of a male sterile trait by genetic modification of C. japonica is a viable approach to address the medical and public health problems of C. japonica polleninduced pollinosis.…”
Section: Introductionmentioning
confidence: 99%
“…The stable transformation of conifers has been reported in several genera, such as Picea, Larix, and Pinus (Malabadi and Nataraja 2007). However, there are only 2 reports on the genetic transformation of C. japonica, which used particle bombardment and an Agrobacteriummediated method (Maruyama et al 2000;Taniguchi et al 2008), whereas the transformation efficiency levels were inadequate. Thus, we attempted to develop a more efficient C. japonica transformation method based on the Agrobacterium-mediated method reported by Taniguchi et al (2008).…”
mentioning
confidence: 99%
“…However, there are only 2 reports on the genetic transformation of C. japonica, which used particle bombardment and an Agrobacteriummediated method (Maruyama et al 2000;Taniguchi et al 2008), whereas the transformation efficiency levels were inadequate. Thus, we attempted to develop a more efficient C. japonica transformation method based on the Agrobacterium-mediated method reported by Taniguchi et al (2008). Recently, it was reported that meropenem, a novel β-lactam antibiotic, is highly effective against Agrobacterium, and it improved transformation efficiencies in tobacco, tomato, rice, and apple compared with those observed by cefotaxime and carbenicillin (Li et al 2011;Ogawa and Mii 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations